Gender differences among elderly in the use of Internet banking services - Angel Fco. Villarejo-Ramos; Bego\~na Peral-Peral; Jorge Arenas-Gaitán; Maria Angeles Ramón-Jerónimo (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The Internet banking has changed the type of relationship between clients and banks. Today it is possible to manage accounts and all of the services online having the opportunity to compare different providers quickly and easily. The future of the Internet bank is in the type of services offered and in the way they interact with clients satisfying their needs. In this work, through a sample of 415 individuals older than 55 years, we analyse the gender gap in the use of Internet Baking and preferences for personal contact as key variables in the explanation of the frequency of use of ten services regularly offered by the Internet banking. Results show the existence of a gender gap in the frequency of use, although the level of autonomy in the preference for personal contact dilutes gender differences for some services.
Keywords: 650; Elderly; Internet banking; gender gap; personal contact